IDENTIFIKASI MISKONSEPSI DAN REMEDIAL TEACHING MATERI KALOR PADA SISWA SMA NEGERI 1 PARIGI TENGAH - Rahmat; Syamsu (Universitas Tadulako, 2021)
This study uses a qualitative and quantitative approach that aims to identify misconceptions and provide remedial teaching to students of SMA Negeri 1 Parigi Tengah. The subjects of this study were students of class X IPA 1 and IPA 2 which consisted of 40 students. The data collection instrument used was reasoned multiple choice and 15 items of interviews accompanied by CRI to determine the level of confidence of the research subjects in answering the questions. After identifying the misconceptions, students who experience misconceptions are given remedial teaching before being given the same test accompanied by interviews with students who experience changes or increases in knowledge. The results obtained when identifying misconceptions are 26.83% of students who have misconceptions, 31.30% of students do not understand the concept, and 41.83% of students who understand the concept. After remedial teaching, students who experienced misconceptions decreased to 13.5%, students who did not understand concepts to 12.67% and students who understood concepts increased to 73.83%. This shows that the provision of remedial teaching is very useful in overcoming student problems in learning where there are still many students who find it difficult to conceptualize physics concepts.